PENGARUH LOKASI USAHA, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN KONSUMEN DI EBOSS BARBERSHOP - Sulanggir Kuning; Ellin Herlina; Hartanto Halim (Journal Of Resource Management, Economics And Business, 2023)
Purpose: Researching, testing and analyzing the variables of business location, service quality, and price on customer satisfaction Research Methodology: This study uses quantitative methods with survey research. The sampling technique in this study uses non-probability sampling using saturated samples with a total sample of 88 respondents who are Eboss barbershop consumers. The analysis data was processed using the SPPS version 26 for windows program. Results: The results showed that business location, service quality, and price had a positive and significant effect on consumer satisfaction partially, by number 0.244; 0.171 and 0.477. Simultaneously obtained a number of 24,461. The results of this study indicate a coefficient of determination of 46.6% explaining that business location, service quality, and price have a positive effect on consumer satisfaction while the remaining 53.4% is influenced by other variables not examined in this study. Limitations: Sample Size: The study used a relatively small sample size of 88 respondents, which may limit the generalizability of the findings to a larger population. A larger sample size would have provided more robust results. Single Location: The study focused on Eboss barbershop, which may limit the generalizability of the findings to other barbershops or businesses in different locations. The results may be specific to this particular establishment and its customer base. Cross-Sectional Design: The study used a cross-sectional design, which provides a snapshot of consumer satisfaction at a specific point in time. Longitudinal studies that track changes in satisfaction over time would offer more insights into the dynamic nature of customer preferences. Contribution: Business Management: The findings of this study can provide valuable insights to barbershop owners and managers in understanding the factors that influence customer satisfaction. By recognizing the significance of business location, service quality, and price, they can make informed decisions to improve customer experience and loyalty. Marketing and Consumer Behavior: The study contributes to the field of marketing and consumer behavior by highlighting the importance of location, service quality, and price in shaping consumer satisfaction. The findings can be useful for marketers and researchers studying consumer preferences and developing strategies to enhance customer satisfaction. Service Industry: The study's findings may be particularly relevant to the service industry, including barbershops, salons, and other customer-oriented businesses. The insights gained from this research can help service providers optimize their operations and offerings to meet customer expectations and improve overall satisfaction levels.